Mother–Child Relationship and Emotion Regulation in Emerging Adults - Shalsabila, Trisnajaya; Novita, Shally; Islaha, Shafia (Faculty of Psychology, Universitas Gadjah Mada, 2026)
Emotion regulation is a critical skill for individuals because it is related to emotion and responsemanagement. The development of emotion regulation can be influenced by many factors, including the relationship betweenmother and child. This research investigated the link between mother–child relationship and emotion regulation inemerging adults, aged 18 to 25 years old. A total of 191 emerging adults participated in the study by completing aquestionnaire that comprised two measurement tools: the Bandung Family Relationship Test (BFRT) and the EmotionRegulation Questionnaire (ERQ). Using this data, the researchers aimed to uncover whether each dimension in themother–child relationship is tied to emotion regulation in emerging adults. Hypothesis testing was conducted usinggeneral linear model (GLM) analysis. The results showed that vulnerability, acknowledgement, and justice inmother–child relationships are related to emotion regulation, specifically cognitive reappraisal and expressivesuppression strategies. Conversely, restrictiveness, affection, and trust were not found to have any interaction withemotion regulation strategies. This research suggests that these dimensions must be adjusted to align with thedevelopmental progression of this stage.